Hubungan Dukungan Keluarga dengan Kualitas Hidup pada Klien Diabetes Mellitus di Puskesmas Srandakan Bantul - Yosahara Ashrivia Ghifaudin (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to examine the relationship between family support and quality of life of patients with diabetes mellitus at the Srandakan Health Center, Bantul, Yogyakarta. Diabetes mellitus (DM) is a chronic metabolic disease that has a significant impact on the physical, psychological, social, and environmental aspects of the patient. The increasing prevalence of DM, especially in the elderly population in Indonesia, demands a more effective and holistic management strategy. Family support has an important role in improving self-care behaviors and adherence to treatment, which has a direct impact on patients' quality of life. This study uses a quantitative correlational analytical design with a cross-sectional approach. An independent variable is family support measured through informational, emotional, instrumental, and appreciative dimensions. Dependent variables are quality of life that include physical, psychological, social, and environmental aspects. The study population consisted of DM patients who visited the Srandakan Health Center. The results of the study are expected to show that supportive family involvement contributes positively to improving the quality of life of patients. These findings provide theoretical and practical implications for the development of nursing care and public health programs, particularly in the context of chronic diseases. This research also emphasizes the importance of comprehensive education and community participation in strengthening the role of the family as the main support system in the management of diabetes mellitus.